El canto de la tierra: W. H. Hudson y el estado natural - Bate, Jonathan (Anales de Literatura Hispanoamericana, 2004)
Against the backdrop of the ecological crisis spawned by modern progress, literature has renewed its representations of the Golden Age and of the lost organic community. The anglo-argentine writer W. H. Hudson, in his novel Green Mansions (1904), offers an early exploration of today’s greatest ecological catastrophe: the destruction of South America’s rainforests, pitting the idealistic but destructive invasion of Abel, the modern man, against the state of nature of the bird-girl Rima. Rima’s call can still be heard at the beginning of the third millenium after Christ.